The mansion : a novel - Boone, Ezekiel (Emily Bestler Books/Atria, 2018)
In this thriller from Ezekiel Boone, author of The Hatching series, a family moves into a home equipped with the world's most intelligent, most cutting-edge, and most intuitive computer ever--with terrifying and catastrophic results.